2022
DOI: 10.3748/wjg.v28.i22.2437
|View full text |Cite
|
Sign up to set email alerts
|

18β-glycyrrhetinic acid regulates mitochondrial ribosomal protein L35-associated apoptosis signaling pathways to inhibit proliferation of gastric carcinoma cells

Abstract: BACKGROUND Gastric carcinoma (GC) is a common gastrointestinal malignancy worldwide. Based on the cancer-related mortality, the current prevention and treatment strategies for GC still show poor clinical results. Therefore, it is important to find effective drug treatment targets. AIM To explore the mechanism by which 18β-glycyrrhetinic acid (18β-GRA) regulates mitochondrial ribosomal protein L35 (MRPL35) related signal proteins to inhibit the proliferation of GC cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Our team previously reported that 18β-glycyrrhetinic acid, a natural drug component, affects the proliferation and metastasis of GC[ 21 ]. PA also appears to be useful as a natural product for the treatment of GC.…”
Section: Introductionmentioning
confidence: 99%
“…Our team previously reported that 18β-glycyrrhetinic acid, a natural drug component, affects the proliferation and metastasis of GC[ 21 ]. PA also appears to be useful as a natural product for the treatment of GC.…”
Section: Introductionmentioning
confidence: 99%
“…8 The cell cycle consists of the following stages: the first gap (G 1 ) phase, which is dominated by the synthesis of RNA and ribosomes; the synthesis (S) phase, which is focused on DNA replication; the second gap (G 2 ) phase, which involves preparation for mitosis; and the mitotic (M) phase. 9 The cell cycle is co-regulated by Cyclin and Cyclindependent kinases (CDKs), in which Cyclin is responsible for coordinating various checkpoints that govern progression through the phases. When the Cyclin-CDK complex interacts with CDK inhibitor proteins, including proteins of the INK4 family and CIP/KIP family, the activity will be inhibited.…”
Section: Introductionmentioning
confidence: 99%
“…Among these processes, the investigation of the cell cycle, for example by following the expression of cell cycle‐related molecules, has provided important clues to the process of neurogenesis, especially during embryonic development 8 . The cell cycle consists of the following stages: the first gap (G 1 ) phase, which is dominated by the synthesis of RNA and ribosomes; the synthesis (S) phase, which is focused on DNA replication; the second gap (G 2 ) phase, which involves preparation for mitosis; and the mitotic (M) phase 9 . The cell cycle is co‐regulated by Cyclin and Cyclin‐dependent kinases (CDKs), in which Cyclin is responsible for coordinating various checkpoints that govern progression through the phases.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some studies have reported that 18β-GRA can inhibit the invasion and migration of GC cells through the ROS/PKC-α/ERK pathway [ 19 ]. Recently, it was found that 18β-GRA can regulate the apoptosis signaling pathway associated with MRPL35, and inhibit GC cells proliferation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%